Employment and Migration in the Border State of Baja California-México - Antonio Escamilla Diaz; Alejandro Mungaray Lagarda; Gerardo Huber Bernal (Research Aspects in Arts and Social Studies Vol. 2, 2022)
With the objective of assessing the impacts of the national migration in the occupation levels, series of occupied population of Baja California were obtained. In order to estimate the numbers for the five municipalities, weights of the employed population were applied to the total population, utilising the ENOE/INEGI report on the employed population for Tijuana and Baja California from 2005 to 2015 as a source of information. The findings demonstrate that the metropolitan zone Tijuana-Tecate-Playas de Rosarito has a common occupational behaviour, whereas Mexicali and Ensenada have distinct occupational behaviours. In addition, changes in the economically active population, the occupied population in the country’s regions, and their impact on the occupation level in the State and each of its municipalities are examined, in a scenario where increases in the unemployment rate are imported from other States ejectors of labour force.